Biodiversity of Marine Mollusks in East Coastal Area of Thanjavur District, Ttamil Nadu, India - Anandaraj, T. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Molluscan fanua of gastropoda and bivalvia were collected from different stations of coastal area in Thanjavur District, Tamil Nadu, India. In the present investigation, 20 species of gastropods fauna and 20 species of bivalvia fauna were recorded September 2011 to December 2011. Among the gastropod a fauna, Bursa crumena followed 15 species was not dominant and five species like Chicoreus ramousus, Murex trapa, Natica tigrina, Olive gibbosa and Tonna dolium was dominant and 11 species was not dominant. The gastropoda fauna maximum density was recorded in station – III and the bivalvia fauna maximum density was recorded in station – II.